2007
DOI: 10.1097/jcp.0b013e3180592ad2
|View full text |Cite
|
Sign up to set email alerts
|

Increased (R)-Methadone Plasma Concentrations by Quetiapine in Cytochrome P450s and ABCB1 Genotyped Patients

Abstract: Steady-state plasma concentrations of (R)- (ie, the active form), (S)-, and (R,S)-methadone were measured in 14 addict patients in methadone maintenance treatment, before and after introduction of quetiapine, administered at a mean dosage of 138 mg/d (SD, 87 mg/d; median, 125 mg/d; range, 50-300 mg/d) during a mean period of 30 days (SD, 8 days; median, 30 days; range, 20-48 days). Eleven patients were genotyped as being CYP2D6 extensive metabolizers (EMs) and 3 patients as poor metabolizers. Eleven patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 25 publications
0
42
1
Order By: Relevance
“…In 14 patients enrolled in MMT, methadone plasma levels were measured before and after introduction of quetiapine (mean dose 138 mg/day, for a mean period of 30 days) 174 . An increase in the (R)-methadone, but not (S)-methadone, concentration to dose ratio was observed.…”
Section: Quetiapinementioning
confidence: 99%
“…In 14 patients enrolled in MMT, methadone plasma levels were measured before and after introduction of quetiapine (mean dose 138 mg/day, for a mean period of 30 days) 174 . An increase in the (R)-methadone, but not (S)-methadone, concentration to dose ratio was observed.…”
Section: Quetiapinementioning
confidence: 99%
“…CYP 2B6 and 2C19 are polymorphically distributed, resulting in subpopulations of efficient and inefficient metabolizers and substances such as paroxetine and quetiapine have been shown to alter the metabolic rate of methadone [17,18]. Each of these factors, stereoselectivity, polymorphism, and drug interactions, may contribute to rates of methadone demethylation and ultimately to variability in the formation of EMDP.…”
Section: Discussionmentioning
confidence: 97%
“…Some clinical studies have suggested there is a likely relationship (155)(156)(157)(158)(159), while others have suggested there is likely not (161)(162)(163)165), and still others propose that ABCB1 polymorphisms are only one of a number of interacting pharmacogenetic determinants influencing methadone pharmacokinetics (160). Despite extensive research, there remains considerable controversy over the functional consequences of various ABCB1 polymorphisms (222)(223)(224)(225).…”
Section: Methadonementioning
confidence: 96%
“…Patients homozygous for the 'T' allele in SNP 1236C>T and carriers of the 3-locus genotype pattern of 'TT-TT-TT' (3435C>T, 2677G>T and 1236C>T polymorphisms) were estimated to have an approximately 7-fold and 5-fold increased chance of requiring higher (>150 mg/day) maintenance methadone doses relative to non-carriers, respectively (156). A Swiss study of 14 MMT subjects found the ABCB1 genotypes 3435 TT, CT, and CC resulted in 3, 23 and 33% increases in (R)-methadone concentration/dose ratios following administration of P-gp substrate quetiapine, respectively (158). Carriers of the variant ABCB1 3435C>T were found to require higher doses of methadone than non-carriers among a population of Han Chinese patients (157), and a pilot study of 178 Taiwanese patients in a MMT program found the ABCB1 2677T allele had positive effects on methadone plasma concentration (159).…”
Section: Methadonementioning
confidence: 98%